2009
DOI: 10.1149/1.3005993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen Content on the Structural and Electrical Properties of Thin Yb[sub 2]O[sub 3] Gate Dielectrics

Abstract: This paper describes the structural properties and electrical characteristics of thin normalYb2normalO3 gate dielectrics deposited on silicon substrates through reactive sputtering. The structural and morphological features of these films were studied, as a function of the growth conditions (three various argon-to-oxygen flow ratios, 10∕15 , 15∕10 , and 20∕5 , and temperatures from 600to800°C ), by X-ray diffraction, atomic force microscopy, and X-ray photoelectron spectroscopy. It was found that normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…In addition, the transparency and optical bandgap of Yb 2 O 3 were also measured ( Figure 3 c). The Yb 2 O 3 shows higher transparency at short wavelength and larger optical bandgap of 5.48 eV, in accord with previous research [ 25 ]. Hence, the increased optical bandgap with Yb incorporation is ascribed to the larger optical bandgap of Yb 2 O 3 than that of In 2 O 3 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the transparency and optical bandgap of Yb 2 O 3 were also measured ( Figure 3 c). The Yb 2 O 3 shows higher transparency at short wavelength and larger optical bandgap of 5.48 eV, in accord with previous research [ 25 ]. Hence, the increased optical bandgap with Yb incorporation is ascribed to the larger optical bandgap of Yb 2 O 3 than that of In 2 O 3 .…”
Section: Resultssupporting
confidence: 92%
“…Besides, the Yb and In share the same valence state of +3, which would not introduce additional electrons [ 16 ]. Meanwhile, Yb 2 O 3 and In 2 O 3 hold the same bixbyite structures and hence low defect densities could be expected [ 16 , 25 ]. Jun et al reported the electrospun indium ytterbium oxide (In-Yb-O) nanofiber TFTs [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated charges at the surface of the gate oxide lm that arise from the electrolyte solution cannot be passed through the lm, thus leading to the change in the channel conductance and current modulation. [13][14][15] However, moisture absorption is a major issue when RE oxides are used as gate dielectrics in CMOS devices, which degrades their electrical performance due to the formation of hydroxides. 16 To avoid the unwanted hydroxide lm, the Zr/Ti ratio of 0.53/0.47 was previously successfully adopted in a sensing lm by our group.…”
Section: Introductionmentioning
confidence: 99%
“…The band gap of the Yb 2 O 3 is around 5 eV. [29] At higher pump power, eight/nine CW 980 nm laser photon absorption process confirms photon avalanche behavior within the synthesized material. Since, the absorption cross-section Yb 3 + is temperature dependent.…”
Section: Uc Emission Studymentioning
confidence: 70%